Pengaruh Edukasi Manajemen Patah Tulang Terhadap Pengetahuan Pasien Di Ruang Bedah Rumah Sakit Umum Cendrawasih Dobo - Yerry Soumokil; Aprilya Fifiyanti Wahelatoan; Selfia Reipilaman (Lembaga Pengembangan Kinerja Dosen, 2023)
Fractures can occur with broken bones where the bone can remain in a closed fracture or outside the skin in open fractures. Fractures of the sharp ends of bones can cause harm to the soft tissues, usually the muscles surrounding the bones are more or less damaged. The nerves and blood vessels that run near the bones can also be injured (Sudiharto, 2020). The purpose of this activity is to provide health education to inpatients who experience fractures at the Cendrawasih Dobo General Hospital so that patients and their families understand fracture management quickly and accurately. The method of implementing this activity is health counseling to patients and their families who experience fractures at the Cendrawasih General Hospital in Dobo. Participants who were seen in this activity were fracture patients and their families at Cendrawasih Dobo General Hospital, totaling 10 people. Based on this community service activity, it can be seen that this activity can increase patient and family knowledge in health counseling related to fracture management.